Lymphocyte-Neutrophil Ratio in the Diagnosis of Tubercular Pleural Effusion in a Tertiary Care Centre: A Descriptive Cross Sectional Study - Jha, Rajneesh; Mehata, Ram Kumar; Koirala, Puru (Birat Journal of Health Sciences, 2021)
Introduction: Tuberculosis is a common infection in our community. Tubercular pleural effusion is the second most common form of extrapulmonary tuberculosis. Among the several causes of exudative pleural effusison tubercular remains the most common form in clinical practice. The aim of this study was to evaluate the significance of lymphocyte-neutrophil ratio(LN ratio) in cases of exudative effusion for diagnosis of tubercular effusion.Methods: This was a hospital based cross sectional studydone in Patients at tertiary care hospital from 1st September 2020 to 1st april 2021after taking ethical clearance from institutional reviw committee. Convienience samplingwas done. Statistical Analysis of data like percentages and frequencies  were used for categorical variables. Mean and SD (standard deviation) were used for describing continuous variables. Inferential statistical tools like Chi-Square test and Student’s t-test were used. P-value of 0.75 is an efficient means of diagnosing tuberculous pleural effusion and its combination with ADA level gives us more accuracy and surety about the diagnosis of tubercular pleural effusion.